Fructans as Natural, Bioactive Cosmeceutical Ingredients - (:unkn) unknown (CAISTER ACADEMIC PRESS, 2019)
Fructans have novel characteristics and have many applications in cosmetic market as bioactive ingredient or rheology and formulation improver. Cosmeceuticals are not only used for aesthetic reasons but also for the treatment of ailments. Here in this chapter we focus on cosmeceuticals, applications, natural polysaccharides and their needs, fructans and their usage and activity in cosmetic formulations. Main attention is paid on fructan based skin care cosmeceuticals (moisturizing, antiaging, and whitening) based on new formulations with natural ingredients. The annual exponential growth of consumers that are fully aware of natural, and bioactive ingredients determines the special impact of this review for evaluation the future of the pharmaceutical industry.
Keywords: ATOPIC-DERMATITIS; DOUBLE-BLIND; MOLECULAR MECHANISMS; HALOMONAS-SMYRNENSIS; MULTILAYER FILMS; SULFATED LEVAN; IN-VITRO; SKIN; OLIGOSACCHARIDES; ANTIOXIDANT